Degradability of Chemicals by Microorganisms in Pond Water - TODA, CHITOSE; YASUI, TERUYO; NAGANO, HIDEO; HASHIZUME, KIYOMATSU; NOZAWA, MASANORI (Eisei kagaku, 1994)
To examine the biodegradation of environmental pollutants, particularly pesticides, by aquatic microbes, water sample from three ponds with different surroundings in Nagoya City were subjected to water quality analysis, classification of microflora and microbial biodegradation tests using the cultivation method (Handai method). Physicochemical studies revealed that the three ponds were class B or C according to the Environmental Standard for Lakes and Marshes. The total phosphorus concentration suggested that they were eutrophic. Gram-negative bacteria were predominant in the microflora of all three, and included microorganisms of Alcaligenes sp., Acinetobacter sp., and Pseudomonas sp. Studies on the microbial biodegradation of pesticides revealed that ethylthiometon and fenitrothion were degraded to a considerable extent in the ponds, while isoxathion and simazine were degraded little. The degree of biodegradation varied among the water samples with the month of collection and the test chemicals used to assess it. Microorganisms of Acinetobacter sp. reportedly degrade environmental pollutants, and many isolates of this genus proved capable of destroying ethylthiometon, isoxathion, fenitrothion and anthracene. These organisms were able to grow vigorously in liquid culture, particularly in the presence of fenitrothion or anthracene.